Reviews (New blackfriars, 1966)
THE GLORIOUS VICTORIES OF AMDA SEYON. KING OF ETHIOPIA, translated and edited by G. W. B. Huntingford THE CATHOLIC CHURCH IN MODERN AFRICA, A Pastoral Theology, by J. Mullin. G. Chapman WITCHCRAFT, EUROPEAN AND AFRICAN, by Geoffrey Parrinder THE FAITH OF THE COUNSELLORS, by Paul Halmos SACRED AND SECULAR, by A. M. Ramsey COLLABORATION WITH TYRANNY IN RABBINIC LAW. by David Daube. (Riddell Memorial Lectures. Newcastle University) THEORIES OF PRIMITIVE RELIGION, by E. E. Evans-Pritchard MISSION IN THE NEW TESTAMENT, by Ferninand Hahn FILMSTRIPS FROM THE BODLEIAN LIBRARY BIBLIA PAUPERUM: Bodleian Library Filmstrips (Roll 173 I) BIBLIA PAUPERUM: Bodleian Selection (Roll 175 I) THE FACE OF GOD I: Bodleian Selection (Roll 179 B) THE FACE OF GOD II: Bodleian Selection (Roll 179 C) THE PHILOSOPHY OF RELIGION, by Thomas McPherson REALITY AND MAN. by S. L. Frank. Faber and Faber